A Lab-Based Multi-Length Scale Approach to Characterize Lithium-Ion Cathode Materials. (7th July 2017) - Randjbar Daemi, Sohrab; Brett, Daniel J.L.; Shearing, Paul R.
Abstract : X-ray computed tomography has emerged as a valuable tool to analyze battery materials. This paper explores the possibilities and limitations offered by a multi-length scale lab-based approach to study a lithium nickel manganese cobalt oxide electrode for lithium ion battery applications. The porosity, tortuosity and particle size distribution are extracted from micro- and nano-CT datasets and discussed in terms of the resolution available for the measurement. This work sets the basis for a range of studies to understand how different manufacturing routes affect the microstructure of the electrode and how this in turn affects battery performance.